2000
DOI: 10.1177/0741088300017001003
|View full text |Cite
|
Sign up to set email alerts
|

“Blinking Out” and “Having the Touch”

Abstract: This interpretive study of two fifth-grade students' intrinsic motivation for writing examines the ways in which children who self-sponsor writing express “flow” experiences associated with writing. Considering a sense of flow seems to address why some children persevere when faced with challenging tasks and why they spend so much time and effort engaged in activities they find interesting. In addition to the challenge of writing, the social context of the classroom influenced opportunities for student-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Flow is, however, critically dependent on a match-up of high demands and high skill (Csikszentmihalyi 1997;Csikszentmihalyi et al 1993). In educational contexts, learner characteristics such as interest (Abbott 2000;Guo and Ro 2008) and curiosity (Egbert 2003;Guo and Ro 2008;Schiefele and Csikszentmihalyi 1994;Webster et al 1993) also play an important role as antecedents of flow.…”
Section: The Experience Of Flowmentioning
confidence: 99%
“…Flow is, however, critically dependent on a match-up of high demands and high skill (Csikszentmihalyi 1997;Csikszentmihalyi et al 1993). In educational contexts, learner characteristics such as interest (Abbott 2000;Guo and Ro 2008) and curiosity (Egbert 2003;Guo and Ro 2008;Schiefele and Csikszentmihalyi 1994;Webster et al 1993) also play an important role as antecedents of flow.…”
Section: The Experience Of Flowmentioning
confidence: 99%
“…This is unfortunate because newer research indicates that a state of flow is associated with academic success [ 56 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Furthermore, a state of flow enhances students’ perceptions of learning, skill development, and satisfaction [ 50 ] and helps them persevere [ 66 ] The most important aspect of flow that affects learning outcomes is the intrinsic reward inherent in flow—the activity itself is rewarding [ 50 ]. Helping students identify their strengths and ways to use them can increase intrinsic motivation [ 67 ].…”
Section: Synching the Mind: Creating Flow To Connect To Content And O...mentioning
confidence: 99%
“…Autonomy within the context of rules and responsibilities enhances flow [ 54 , 66 , 71 , 72 ]. Educational research shows a positive association between achievement and autonomy [ 73 ].…”
Section: Synching the Mind: Creating Flow To Connect To Content And O...mentioning
confidence: 99%
“…Some ethnographic research has looked at students responding to specific tasks in schools, primarily to demonstrate the individuality, intelligence, and creative struggle of writers of various ages in making sense of expectations and situations (for example, Abbott, 2000), but this work has not yet added up into a developmental picture, though it does suggest processes of learning through sense-making and participation. Also some research has demonstrated the importance of experiences outside schooling or among peers within school but outside organized curricula (for example, Finders, 1996); however, this work has not yet been integrated with the learning in school, nor has it gotten much beyond demonstration of the existence of non-curricular writing development to be factored into an integrated model.…”
Section: Disentangling Curriculum and Developmentmentioning
confidence: 99%
“…Algunas investigaciones etnográficas han estudiado la respuesta de estudiantes a tareas específicas en las escuelas, principalmente para demostrar la individualidad, inteligencia y esfuerzo creativo de escritores de diversas edades en la búsqueda de dar sentido a sus expectativas y a distintas situaciones (por ejemplo, Abbott, 2000), pero este trabajo aún no ha logrado proporcionar un panorama evolutivo, aunque sugiere procesos de aprendizaje a través de la búsqueda de sentido y la participación. Además, algunas investigaciones han demostrado la importancia de las experiencias fuera de la escuela o entre iguales, dentro de la escuela, pero fuera de los currículos organizados (por ejemplo, Finders, 1996); no obstante, este trabajo aún no se ha integrado con el aprendizaje en la escuela, ni ha llegado mucho más allá de la demostración de la existencia de una evolución no curricular de la escritura, que se pueda incluir en un modelo integrado.…”
Section: Desenmarañando Currículum Y Evoluciónunclassified